Evaluation of meat quality of weaned rabbits administered different concentrations of probiotic strain (Saccharomyces boulardii) - Zhiri-Jiya Elisha; Chinma Chiemela-Enyinnaya; Sanusi Ahmed (Biotechnology in Animal Husbandry, 2018)
The meat quality and sensory properties of weaned rabbits administered different concentrations/cell count of probiotic Saccharomyces boulardii (flora norm) were investigated. A total of 36 mixed breeds of rabbits were randomly divided to four treatments with three replicates and three rabbits per replicate. The weaned rabbits were fed the same diet. Treatments T1, T2, T3 and T4 had zero (0) concentration/cell count of probiotic, 1ml each of 160 x106 it is%1.6 x 108 cfu/ml concentration of probiotic, 1 ml each of 80 x106 cfu/ml =8.0 x 107 cfu/ml of probiotic and 1 ml each of 40 x 106 cfu/ml concentration of probiotic, respectively. The administration of the probiotic was done once every 14 days. Results obtained showed that there was no significant difference in moisture and crude protein content of meat from rabbits while ether extract differed significantly (P<0.05). The physical properties, cooking yield, cooking loss and water holding capacity were not significantly (P>0.05) influenced by concentrations of probiotics while pH and thermal shortening were significantly (P<0.05) influenced. All the sensory parameters measured were significantly (P<0.05) different. It was found that oral administration of probiotic Saccharomyces boulardii (flora norm) at 4 mg/ml 80 x 106 cfu/ml concentration improved meat qualities and overall acceptability of rabbit meat.